2017
DOI: 10.2147/jpr.s118846
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of reaching is disturbed in complex regional pain syndrome: a single-case study

Abstract: ObjectiveDisturbance of goal-directed motor control may cause or exacerbate pathological pain in patients with complex regional pain syndrome (CRPS). We conducted a single-case study about motor control involved in reaching with a patient with CRPS in an upper limb.MethodsUsing a three-dimensional measurement system, we recorded reaching movement trajectories of the intact and affected hand before and after pain alleviation by therapeutic nerve blockade. We assessed degrees of tremor in the acceleration phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Repeated painful surgery on the extremity would require the discussion of a Complex Regional Pain Syndrome (CRPS), but the complete absence of trophic disturbances is incongruous. Case reports of tremor have been described but only after markable deafferentation not fitting well in this case [24]. There were no signs of bradykinesia and Parkinson's syndrome, nor evidence of essential or enhanced physiological tremor.…”
Section: Case Reportmentioning
confidence: 52%
See 1 more Smart Citation
“…Repeated painful surgery on the extremity would require the discussion of a Complex Regional Pain Syndrome (CRPS), but the complete absence of trophic disturbances is incongruous. Case reports of tremor have been described but only after markable deafferentation not fitting well in this case [24]. There were no signs of bradykinesia and Parkinson's syndrome, nor evidence of essential or enhanced physiological tremor.…”
Section: Case Reportmentioning
confidence: 52%
“…A passive fixation of the hand led to an increase of the symptoms in the arm and in the shoulder. This phenomenon is described as "whack-amole" sign in patients with functional movement disorders (Video Entrainment_Coactivation) [24].…”
Section: Case Reportmentioning
confidence: 99%
“…Previous studies have demonstrated that patients with strokes or pathological pain suffer distorted limb ownership and an inability to perceive their affected limbs as a part of their bodies (Galer and Jensen, 1999 ; Frettlöh et al, 2006 ; Burin et al, 2015 ). Additionally, other studies showed a decrease of movements accuracy (Bank et al, 2015 ; Osumi et al, 2017 ). This our result may be useful for grasping the extent of temporal incongruence of the patient’s sensory movement by evaluating the change in body perception and movement disorders felt by the patient.…”
Section: Discussionmentioning
confidence: 84%
“…In general, individuals with a musculoskeletal disorder tend to make their daily movements slowly. The experience of pain after movements can slow their daily movements 29,30 , but the daily movements remain slow even after pain alleviation 31,32 . It has been suggested that not pain but rather the fear of movement makes daily movements slow 23,33 .…”
Section: Discussionmentioning
confidence: 99%